Detection of Helicobacter pylori in City Water, Dental Units' Water, and Bottled Mineral Water in Isfahan, Iran - Ahmad Reza Bahrami; Ebrahim Rahimi; Hajieh Ghasemian Safaei (The Scientific World Journal)
Helicobacter pylori infection in human is one of the most common infections worldwide. However, the origin and transmission of this bacterium has not been clearly explained. One of the suggested theories is transmission via water. This study was conducted to determine the prevalence rate of H. pylori in tap water, dental units' water, and bottled mineral water in Iran. In the present study, totally 200 water samples were collected in Isfahan province and tested for H. pylori by cultural method and polymerase chain reaction (PCR) by the detection of the ureC (glmM) gene. Using cultural method totally 5 cultures were positive. Two out of 50 tap water samples (4%), 2 out of 35 dental units' water (5.8%) samples, and 1 out of 40 (2.5% ) from water cooler in public places were found to be contaminated with H. pylori. H. pylori ureC gene was detected in 14 (7%) of water samples including 5 tap water (10%), 4 dental units' water (11.4%), 1 refrigerated water with filtration, and 4 (10%) water cooler in public places samples. This may be due to the coccoid form of bacteria which is detected by PCR method.